Migrações internas e malária urbana - Bahia, Brasil Internal migration and urban malaria - Bahia, Brazil - Sebastião Loureiro de Souza; Maria Inês Costa Dourado; Ceci Vilar Noronha (Universidade de São Paulo, 1986)
Estuda-se as características sócio-econômicas dos indivíduos acometidos pela malária, em 1983, na área urbana de Camaçari - Bahia, Brasil, com destaque para os subgrupos migrantes e não migrantes. As condições de vida precárias de ambos os subgrupos são apontadas como os determinantes do surto de malária desencadeado no local. It is proposed to study the socio-economic characteristics of individuals who were infected with malaria in the urban area of Camaçari, Bahia, Brazil, in 1983. Special emphasis being given to the subgroups of migrants and nonmigrants. The precarious living conditions of both subgroups are identified as determinative of the malaria outbreak which occurred there.